Tales and Novels of J. de La Fontaine $1 (BVolume 12s - La Fontaine, Jean de, 1621-1695 (Salt Lake City, UT : Project Gutenberg, 2004)
"Tales and Novels of J. de La Fontaine $1 (BVolume 12" by Jean de La Fontaine is a collection of fables and tales penned during the 17th century, a time marked by the blossoming of French literature and culture. This volume combines the moralistic storytelling of La Fontaine with elements of humor and satire, addressing themes such as human nature, folly, and social critique through imaginative narratives. The likely topics of the book revolve around the absurdity of certain societal norms and the behavior of both the clergy and laypeople. In this volume, La Fontaine presents two main works: "The Monks of Catalonia" and "The Cradle." "The Monks of Catalonia" tells a tale of deceiving and cunning monks who manipulate local women into paying them tithes under the guise of religious duty, leading to unexpected chaos when husbands discover the truth. The narrative satirizes the hypocrisy of religious authorities and the gullibility of those who follow them. In "The Cradle," a comedic mix-up occurs when two young lovers and a married couple fall into a series of misunderstandings and romantic entanglements at a humble inn, highlighting themes of trust, fidelity, and the complexity of human relationships. Through these stories, La Fontaine cleverly reveals the follies and moral dilemmas faced by individuals in society. (This is an automatically generated summary.)s
The Monks of Catalonia -- The Cradle.
Release date is 2004-03-01
This eBook was produced by David Widger
Keywords: French poetry -- Translations into English; Fables, French -- Translations into English